Copolymerized polyetherketone ultrathin film raw material and preparation method thereof, copolymerized polyetherketone ultrathin film and preparation method thereof, and application of copolymerized polyetherketone ultrathin film in field of acoustic vibrating diaphragms
By using copolypolyetherketone ultra-thin film raw materials and combined with twin screw extrusion technology, a copolyetherketone ultra-thin film with excellent high temperature resistance and toughness was prepared, which solved the problem of insufficient performance of polyaryletherketone in high temperature environments and was suitable for the field of acoustic diaphragm.
Patent Information
- Application Number
- CN202411497806.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Polyaryletherketone has insufficient high temperature resistance and toughness in high temperature harsh environments, which limits its application range.
The ultra-thin film raw materials of copolyetherketone, including copolyetherketone polymer, viscosity regulator resin, heat stabilizer and lubricant, are used to prepare ultra-thin films through twin-screw extrusion technology to improve their high temperature resistance and toughness.
The prepared copolyetherketone ultra-thin film has excellent high temperature resistance and high toughness, and is suitable for the acoustic diaphragm field, significantly improving its performance in high temperature environments.
Smart Images

Figure CN119592045A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer materials and preparation thereof, and specifically relates to a copolymerized polyetherketone ultra-thin film raw material and a preparation method thereof, a copolymerized polyetherketone ultra-thin film and a preparation method thereof, and applications in the field of acoustic diaphragms. Background Art
[0002] Polyetherketone is a high molecular polymer whose main chain is formed by alternating ether bonds and ketone bonds. As a type of polyaryletherketone, polyetherketone is widely used due to its high performance. It has excellent mechanical properties, corrosion resistance, high temperature resistance and electrical insulation properties, and exhibits excellent durability in extremely harsh environments.
[0003] However, with the development of production and life, the application scenarios of polyether ketone are constantly expanding, and it is mostly used in high-temperature and harsh environments. The high temperature resistance and toughness of polyaryletherketone have become the shortcomings restricting its application. Summary of the invention
[0004] The object of the present invention is to provide a copolymer polyether ketone ultra-thin film raw material and a preparation method thereof, a copolymer polyether ketone ultra-thin film and a preparation method thereof, and applications in the field of acoustic diaphragms. The copolymer polyether ketone ultra-thin film raw material provided by the present invention and the prepared copolymer polyether ketone ultra-thin film have excellent high temperature resistance and toughness.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a copolymerized polyetherketone ultra-thin film raw material, which comprises, by weight, 100 parts of a copolymerized polyetherketone polymer, 2 to 6 parts of a viscosity modifier resin, 0 to 1 part of a heat stabilizer, and 0 to 2 parts of a lubricant; the structure of the viscosity modifier resin is shown in Formula I:
[0007]
[0008] In formula I, the value range of n is 10-60.
[0009] Preferably, the structure of the copolymerized polyetherketone polymer is as shown in Formula A:
[0010]
[0011] In formula A, x=1 to 10%.
[0012] Preferably, the preparation method of the viscosity modifier resin is: 4,4'-dihydroxybenzophenone, a viscosity modifier resin monomer, a water-carrying agent, a catalyst and a first solvent are mixed and sequentially subjected to azeotropic dehydration reaction and polymerization reaction; the structure of the viscosity modifier resin monomer is shown in Formula II:
[0013]
[0014] Preferably, the molar ratio of the viscosity modifier resin monomer to 4,4'-dihydroxybenzophenone is 1.0-1.25:1; the volume ratio of the water-carrying agent to the first solvent is 15-30:100; and the molar ratio of the catalyst to 4,4'-dihydroxybenzophenone is 1.0-1.5:1.
[0015] Preferably, the temperature of the azeotropic dehydration reaction is 160-180° C., and the insulation reaction time is 1-3 hours; the temperature of the polymerization reaction is 220-230° C., and the insulation reaction time is 8-12 hours.
[0016] The present invention also provides a method for preparing the copolymerized polyetherketone ultra-thin film raw material described in the above scheme, comprising the following steps:
[0017] The copolymerized polyetherketone polymer, viscosity modifier resin, heat stabilizer and lubricant are mixed and dried to obtain a premix; the premix is melt-extruded and granulated to obtain the copolymerized polyetherketone ultra-thin film raw material.
[0018] Preferably, the melt extrusion is twin-screw extrusion; the equipment used for the twin-screw extrusion is a twin-screw extruder; the temperature of the front section of the barrel of the twin-screw extruder is 280-290°C, the temperature of the middle section of the barrel is 355-365°C, the temperature of the rear end of the barrel is 370-385°C, and the die temperature is 380-400°C; the screw speed of the twin-screw extruder is 60-80rpm, and the screw feeding speed is 40-45rpm.
[0019] The present invention also provides a copolymer polyether ketone ultra-thin film, which is prepared from a copolymer polyether ketone ultra-thin film raw material; the copolymer polyether ketone ultra-thin film raw material is the copolymer polyether ketone ultra-thin film raw material described in the above scheme or the copolymer polyether ketone ultra-thin film raw material obtained by the preparation method described in the above scheme; the thickness of the copolymer polyether ketone ultra-thin film is 9 to 300 μm.
[0020] The present invention also provides a method for preparing the copolymerized polyetherketone ultra-thin film described in the above scheme, comprising the following steps:
[0021] The copolymerized polyetherketone ultra-thin film raw material is tape-cast to obtain the copolymerized polyetherketone ultra-thin film.
[0022] The present invention also provides the use of the copolymerized polyetherketone ultra-thin film described in the above scheme or the copolymerized polyetherketone ultra-thin film obtained by the preparation method described in the above scheme in the field of acoustic diaphragms.
[0023] The invention provides a copolymerized polyetherketone ultra-thin film raw material. The copolymerized polyetherketone ultra-thin film raw material provided by the invention has reasonable compatibility, low cost and easy to obtain raw materials.
[0024] The present invention also provides a method for preparing the copolymerized polyetherketone ultra-thin film raw material described in the above scheme. The preparation method provided by the present invention has simple steps, convenient operation and good feasibility.
[0025] The present invention also provides a copolymerized polyetherketone ultra-thin film. The copolymerized polyetherketone ultra-thin film provided by the present invention is made of the copolymerized polyetherketone ultra-thin film raw material described in the above scheme, and has excellent high temperature resistance and high toughness, outstanding high temperature wear resistance, and excellent comprehensive performance.
[0026] The present invention also provides a method for preparing the copolymerized polyetherketone ultra-thin film of the above scheme. The preparation method provided by the present invention has low cost, high production efficiency and is suitable for industrial production.
[0027] The present invention also provides the use of the copolymerized polyetherketone ultra-thin film described in the above scheme or the copolymerized polyetherketone ultra-thin film obtained by the preparation method described in the above scheme in the field of acoustic diaphragms. The copolymerized polyetherketone ultra-thin film provided by the present invention has excellent high temperature resistance and high toughness, and is suitable for use in the field of acoustic diaphragms. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 This is the NMR spectrum of the viscosity modifier resin monomer prepared in Example 1;
[0030] Figure 2 DSC spectrum (left) and TGA spectrum (right) of viscosity modifier resin;
[0031] Figure 3 The viscosity data of the copolymerized polyetherketone ultra-thin film raw materials of the 9 groups of formulations in Table 1;
[0032] Figure 4 This is a photo of the appearance of the copolymerized polyetherketone ultra-thin film prepared in Example 4;
[0033] Figure 5 This is the infrared spectrum of the copolymerized polyetherketone ultra-thin film prepared in Example 4;
[0034] Figure 6 This is a test diagram of the dynamic thermomechanical properties of the copolymerized polyetherketone ultra-thin film prepared in Example 4;
[0035] Figure 7 A comparison chart of the frequency response curves of the earphone core (top), receiver (middle), speaker (bottom) prepared in Application Examples 1 to 3 and the AAC production line products. DETAILED DESCRIPTION
[0036] The invention provides a copolymerized polyetherketone ultra-thin film raw material, which comprises, by weight, 100 parts of a copolymerized polyetherketone polymer, 2 to 6 parts of a viscosity modifier resin, 0 to 1 part of a heat stabilizer and 0 to 2 parts of a lubricant.
[0037] The copolymerized polyetherketone ultra-thin film raw material provided by the present invention comprises 100 parts of copolymerized polyetherketone polymer; the copolymerized polyetherketone polymer is preferably a polyetherketone polymer prepared according to Chinese patent CN110156981A; the structure of the copolymerized polyetherketone polymer is preferably as shown in formula A:
[0038]
[0039] In formula A, x=1 to 10%.
[0040] Based on the mass fraction of the copolymerized polyetherketone polymer, the copolymerized polyetherketone ultra-thin film raw material provided by the present invention includes 2 to 6 parts of viscosity modifier resin, specifically 2 parts, 3 parts, 4 parts, 5 parts or 6 parts.
[0041] In the present invention, the structure of the viscosity modifier resin is as shown in Formula I:
[0042]
[0043] In formula I, the value range of n is 10-60.
[0044] In the present invention, the viscosity modifier resin is preferably prepared by mixing 4,4'-dihydroxybenzophenone, a viscosity modifier resin monomer, a water carrier, a catalyst and a first solvent (obtaining a first mixture) and sequentially subjecting the mixture to azeotropic dehydration reaction and polymerization reaction.
[0045] In the present invention, the structure of the viscosity modifier resin monomer is as shown in Formula II:
[0046]
[0047] In the present invention, the viscosity modifier resin monomer is preferably prepared by mixing 3,4',5-trifluorobenzophenone, phenol, potassium carbonate and a second solvent and subjecting them to a reflux reaction.
[0048] In the present invention, the molar ratio of 3,4',5-trifluorobenzophenone to phenol is preferably 1:0.9-1, specifically 1:0.9, 1:0.92, 1:0.94, 1:0.96, 1:0.98 or 1:1.
[0049] In the present invention, the molar ratio of 3,4',5-trifluorobenzophenone to potassium carbonate is preferably 1:1 to 1.3, specifically 1:1, 1:1.1, 1:1.2 or 1:1.3.
[0050] In the present invention, the second solvent is preferably N,N-dimethylacetamide (DMAc).
[0051] In the present invention, the molar ratio of the 3,4',5-trifluorobenzophenone to the second solvent is preferably 1:45-55, specifically 1:45, 1:50 or 1:55.
[0052] In the present invention, the temperature of the reflux reaction is preferably 160-165° C., and the insulation reaction time is preferably 2-5 hours, specifically 2 hours, 3 hours, 4 hours or 5 hours; the chemical reaction equation of the reflux reaction is as follows:
[0053]
[0054] In the present invention, the reflux reaction is preferably carried out in an inert atmosphere; the inert atmosphere preferably includes one or both of nitrogen and argon.
[0055] In the present invention, after the reflux reaction, the obtained reaction mixture is preferably precipitated, washed with water, eluted and dried (referred to as the first drying) in sequence.
[0056] In the present invention, the precipitation is preferably: slowly pouring the reaction mixture into deionized water for precipitation, and collecting the precipitate; the water used for washing is preferably hot deionized water; the temperature of the hot deionized water is preferably 90-100°C; the eluting reagent is preferably dichloromethane; the first drying is preferably drying; the drying temperature is preferably 50-65°C, and the heat preservation and drying time is preferably 3-6h.
[0057] In the present invention, the molar ratio of the viscosity modifier resin monomer to 4,4'-dihydroxybenzophenone is preferably 1.0 to 1.25:1, specifically 1.0:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1 or 1.25:1.
[0058] In the present invention, the water-carrying agent is preferably a benzene homologue; the benzene homologue preferably includes one or more of toluene and xylene.
[0059] In the present invention, the volume ratio of the water-carrying agent to the first solvent is preferably 15 to 30:100, specifically 15:100, 20:100, 25:100 or 30:1000.
[0060] In the present invention, the catalyst is preferably a carbonate; the carbonate preferably includes one or both of potassium carbonate (K2CO3) and sodium carbonate.
[0061] In the present invention, the molar ratio of the catalyst to 4,4'-dihydroxybenzophenone is preferably 1.0 to 1.5:1, specifically 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1.
[0062] In the present invention, the first solvent is preferably sulfone; the sulfone is preferably sulfolane (TMS).
[0063] In the present invention, the solid content of the first mixture is preferably 15-30 wt %, specifically 15%, 20%, 25% or 30%.
[0064] In the present invention, the temperature of the azeotropic dehydration reaction is preferably 160-180°C, specifically 160°C, 165°C, 170°C, 175°C or 180°C, and the insulation reaction time is preferably 1-3 hours, specifically 1 hour, 1.5 hours, 2 hours, 2.5 hours and 3 hours.
[0065] In the present invention, the azeotropic dehydration reaction is preferably carried out under stirring conditions; the stirring speed is preferably 75 to 100 rpm, specifically 85 rpm or 95 rpm; the azeotropic dehydration reaction is preferably carried out in an inert atmosphere; the inert atmosphere preferably includes one or both of nitrogen and argon.
[0066] In the present invention, the azeotropic dehydration reaction preferably further comprises dehydrating the obtained reaction system. In the present invention, the water generated by the azeotropic dehydration reaction is removed by dehydrating.
[0067] In the present invention, the polymerization reaction temperature is preferably 220-230°C, specifically 220°C, 222°C, 224°C, 226°C, 228°C or 230°C, and the insulation reaction time is preferably 8-12 hours, specifically 8 hours, 9 hours, 10 hours, 11 hours or 12 hours; the chemical reaction equation of the azeotropic dehydration and polymerization reaction is as follows:
[0068]
[0069] In the present invention, the polymerization reaction is preferably carried out under stirring conditions; the stirring speed is preferably 230-250 rpm; the polymerization reaction is preferably carried out in an inert atmosphere; the inert atmosphere preferably includes one or both of nitrogen and argon.
[0070] In the present invention, the polymerization reaction preferably includes heating the reaction system before the polymerization reaction; the heating rate is preferably 1-3°C / min, specifically 1°C / min, 2°C / min or 3°C / min; the heating is preferably carried out under stirring conditions; the stirring speed is preferably 170-200rpm.
[0071] In the present invention, the polymerization reaction preferably includes post-treatment; the post-treatment preferably includes: pouring the product (polymer solution) obtained from the polymerization reaction into water while hot to obtain a solid polymer, crushing the solid polymer and then extracting, washing and drying (referred to as the second drying) in sequence.
[0072] In the present invention, the water is preferably deionized water; the volume ratio of the polymer solution to water is preferably not less than 1:8, and specifically can be 1:8, 1:9, 1:10, 1:11 or 1:12.
[0073] In the present invention, the reagent used for the extraction is preferably boiling ethanol; the number of extractions is preferably 4 to 10 times, specifically 4 times, 6 times, 8 times or 10 times.
[0074] In the present invention, the washing water is preferably boiling water; the boiling water is preferably boiled deionized water; the number of washing times is preferably 4 to 10 times, specifically 4 times, 6 times, 8 times or 10 times.
[0075] In the present invention, the second drying is preferably oven drying; the oven drying temperature is preferably 100-120° C., specifically 110° C., and the heat preservation and drying time is preferably 10-12 h, specifically 11 h.
[0076] Based on the mass fraction of the copolymerized polyetherketone polymer, the copolymerized polyetherketone ultra-thin film raw material provided by the present invention includes 0 to 1 part of a heat stabilizer, specifically 0 part, 0.1 part, 0.3 part, 0.5 part, 0.7 part, 0.9 part or 1 part.
[0077] In the present invention, the heat stabilizer is preferably the commercially available heat stabilizer Doverphos S-9228.
[0078] Based on the mass fraction of the copolymerized polyetherketone polymer, the copolymerized polyetherketone ultra-thin film raw material provided by the present invention includes 0 to 2 parts of lubricant, specifically 0 parts, 0.1 parts, 0.3 parts, 0.5 parts, 0.7 parts, 0.9 parts, 1.2 parts, 1.5 parts, 1.8 parts or 2 parts.
[0079] In the present invention, the lubricant is preferably the commercially available lubricant Dow Corning RM4-7081.
[0080] The present invention also provides a method for preparing the copolymerized polyetherketone ultra-thin film raw material described in the above scheme, comprising the following steps:
[0081] The copolymerized polyetherketone polymer, the viscosity modifier resin, the heat stabilizer and the lubricant are mixed and dried to obtain a premix;
[0082] The premix is melt-extruded and then granulated to obtain the copolymerized polyetherketone ultra-thin film raw material.
[0083] The present invention mixes the copolymerized polyetherketone polymer, the viscosity modifier resin, the heat stabilizer and the lubricant (referred to as the first mixing) and then dries (referred to as the third drying) to obtain a premix. In the present invention, the first mixing time is preferably 0.5 to 1.5 hours, specifically 0.5 hours, 0.7 hours, 0.9 hours, 1.0 hours, 1.1 hours, 1.3 hours or 1.5 hours; the first mixing equipment is preferably a planetary mixer.
[0084] In the present invention, the third drying is preferably oven drying; the drying temperature is preferably 100-200°C, specifically 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, and the heat preservation and drying time is preferably 3-8 hours, specifically 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours.
[0085] After obtaining the premix, the present invention melt-extrudes the premix and then granulates it to obtain the copolymerized polyetherketone ultra-thin film raw material. In the present invention, the melt extrusion is twin-screw extrusion; the equipment used for the twin-screw extrusion is preferably a twin-screw extruder; the twin-screw extruder is preferably preheated before use; the target temperature of the preheating is preferably 380-400°C, specifically 390°C.
[0086] In the present invention, the temperature of the front section of the barrel of the twin-screw extruder is preferably 280-290°C, specifically 280°C, 284°C, 287°C or 290°C, the temperature of the middle section of the barrel is preferably 355-365°C, specifically 355°C, 358°C, 361°C or 365°C, the temperature of the rear end of the barrel is preferably 370-385°C, specifically 375°C or 380°C, and the die temperature is preferably 380-400°C, specifically 380°C, 385°C, 390°C, 395°C or 400°C.
[0087] In the present invention, the screw speed of the twin-screw extruder is preferably 60-80 rpm, specifically 60 rpm, 65 rpm, 70 rpm, 75 rpm or 80 rpm, and the screw feeding speed is preferably 40-45 rpm, specifically 43 rpm. The present invention ensures that the raw materials are fully plasticized and evenly mixed through twin-screw extrusion, and the mixed material is extruded from the die and shaped through the die.
[0088] In the present invention, the melt extrusion preferably further comprises cooling the product; the cooling is preferably water cooling; and the final temperature of the cooling is preferably room temperature.
[0089] In the present invention, the target particle size of the granulation is preferably 0.5 to 1 cm.
[0090] The present invention also provides a copolymer polyether ketone ultra-thin film, which is prepared from a copolymer polyether ketone ultra-thin film raw material; the copolymer polyether ketone ultra-thin film raw material is the copolymer polyether ketone ultra-thin film raw material described in the above scheme or the copolymer polyether ketone ultra-thin film raw material obtained by the preparation method described in the above scheme; the thickness of the copolymer polyether ketone ultra-thin film is 9 to 300 μm.
[0091] In the present invention, the thickness of the copolymerized polyetherketone ultra-thin film is preferably 9 to 290 μm, specifically 9 μm, 10 μm, 20 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm or 290 μm.
[0092] In the present invention, the width of the copolymerized polyetherketone ultra-thin film is preferably 10 to 100 cm, specifically 10 cm, 20 cm, 40 cm, 60 cm, 80 cm or 100 cm.
[0093] The present invention also provides a method for preparing the copolymerized polyetherketone ultra-thin film described in the above scheme, comprising the following steps:
[0094] The copolymerized polyetherketone ultra-thin film raw material is tape-cast to obtain the copolymerized polyetherketone ultra-thin film.
[0095] In the present invention, the equipment used for the cast molding is preferably an extruder; the feeding section temperature of the extruder is preferably 330-350°C, specifically 330°C, 335°C, 340°C, 345°C or 350°C, the compression section temperature is preferably 395-405°C, specifically 395°C, 400°C or 405°C, the homogenization section temperature is preferably 405-415°C, specifically 405°C, 410°C or 415°C, the extrusion die temperature is preferably 395-405°C, specifically 395°C, 400°C or 405°C, the melt pump temperature is preferably 395-405°C, specifically 395°C, 400°C or 405°C, the filter screen temperature is preferably 395-405°C, specifically 395°C, 400°C or 405°C, the hot roller temperature is preferably 155-165°C, specifically 155°C, 160°C or 165°C.
[0096] In the present invention, the screw torque of the extruder is preferably 60-80Nm, specifically 60Nm, 65Nm, 70Nm, 75Nm or 80Nm, the screw feeding speed is preferably 40-45rpm, specifically 43rpm, and the screw speed is preferably 60-80rpm, specifically 60rpm, 65rpm, 70rpm, 75rpm or 80rpm.
[0097] In the present invention, the casting process preferably further comprises winding up the obtained molded product.
[0098] In the present invention, the preparation of the copolymerized polyetherketone ultra-thin film is preferably carried out in a dust-free experimental environment of Class 10,000 or above.
[0099] The present invention also provides the use of the copolymerized polyetherketone ultra-thin film described in the above scheme or the copolymerized polyetherketone ultra-thin film obtained by the preparation method described in the above scheme in the field of acoustic diaphragms.
[0100] The copolymerized polyetherketone ultra-thin film provided by the present invention has excellent high temperature resistance and high toughness, and is suitable for use in the field of acoustic diaphragms, and can be specifically used in products such as earphone cores, receivers or speakers.
[0101] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0102] Example 1
[0103] (1) Preparation of viscosity modifier resin monomer:
[0104] 3,4',5-trifluorobenzophenone (7.08 g, 30 mmol), phenol (2.82 g, 30 mmol) and K2CO3 (4.35 g, 30 mmol) were added to 120 mL of DMAc, and heated under reflux for 3 hours under nitrogen protection to obtain a mixture, which was slowly poured into deionized water. The precipitate was collected and washed with hot deionized water (temperature of 100°C) to obtain a crude product, which was then eluted with dichloromethane and dried at 50°C for 6 hours to obtain 6.96 g of a viscosity modifier resin monomer, a light yellow solid, and its NMR spectrum is as follows: Figure 1 As shown. Figure 1 It can be seen that the present invention successfully prepares a viscosity modifier resin monomer, the structure of which is shown in Formula II.
[0105] (2) Preparation of viscosity modifier resin:
[0106] 4,4'-dihydroxybenzophenone (6.42 g, 30 mmol), the viscosity modifier resin monomer (9.31 g, 30 mmol), water-carrying toluene (11.25 mL) and catalyst K2CO3 (4.95 g, 36 mmol) were added to solvent TMS (37.5 mL), and stirred at 170°C and 100 rpm for 2 hours under the protection of inert gas (nitrogen), and the water generated by the reaction was removed. Then, the temperature was raised to 220°C at a rate of 1°C / min while stirring at 200 rpm, and the polymerization reaction was carried out for 10 hours under stirring at 240 rpm to obtain a polymer solution. The polymer solution is poured into a large amount of deionized water while hot (the volume ratio of the polymer solution to the deionized water is 1:8), and the solid-liquid separation is performed to obtain a solid polymer powder. The solid polymer powder is crushed, and then extracted with boiling ethanol for 10 times, washed with boiling deionized water for 10 times, and dried at 110° C. for 11 hours to obtain the viscosity modifier resin, the structure of which is shown in Formula I, and the DSC spectrum and TGA spectrum thereof are shown in Figure 2 As shown. Figure 2 It can be seen that the viscosity modifier resin has a glass transition temperature of 128.7° C. and a 5% thermal decomposition temperature of 494.0° C., which confirms that the viscosity modifier resin of the present invention can be stably present in the subsequent granulation and film-making processes.
[0107] (3) Preparation of copolymerized polyetherketone polymer:
[0108] 1314 g of diphenyl sulfone was weighed and added into a three-necked flask equipped with mechanical stirring, argon gas inlet and water device, and heated to 125° C. to melt the diphenyl sulfone from solid to liquid, which was used as the reaction solvent.
[0109] Sodium carbonate (127.19 g, 1.2 mol), potassium carbonate (1.38 g, 0.01 mol), p-hydroxybenzophenone (212.08 g, 0.99 mol), 4,4'-difluorobenzophenone (222.56 g, 1.02 mol), bisphenol fluorene (3.5 g, 0.01 mol), and 280 mL of xylene were weighed respectively, added to a three-necked flask in sequence under an argon atmosphere, heated and stirred, and heated to 150 °C. React for 0.5h, react at 170℃ for 0.5h, react at 210℃ for 2h, react at 225℃ for 1h, react at 250℃ for 1h, react at 280℃ for 1h, react at 290℃ for 1h, react at 305℃ for 0.5h, then discharge the material into deionized water, dry the crude product naturally at room temperature, grind it with a high-speed blender, wash it with acetone and boiled deionized water for 5 times each, put it into a vacuum oven and dry it at 100℃ for 12h, and dry it to obtain a copolymerized polyether ketone polymer.
[0110] (4) Preparation of copolymerized polyetherketone ultra-thin film raw materials:
[0111] In terms of mass fractions, 100 parts of copolymerized polyetherketone polymer, 2 parts of viscosity modifier resin prepared in Example 1, 0 (or 0.05 or 0.1) parts of commercially available heat stabilizer Doverphos S-9228 and 0 (or 1 or 2) parts of commercially available lubricant Dow Corning RM4-7081 were mixed for 1 hour using a planetary mixer, dried at 150°C for 4 hours, and then added to a twin-screw extruder preheated to 380°C, and the screw speed (70rpm), screw feeding speed (40rpm), barrel temperature (front section 280°C, middle section 365°C, rear end 385°C), and die temperature (390°C) were controlled. The resulting mixture was extruded from the die, shaped and cooled by the die, and then granulated to obtain a copolymerized polyetherketone ultra-thin film raw material (referred to as copolymerized PEK).
[0112] Example 2
[0113] (1) Preparation of viscosity modifier resin:
[0114] 4,4'-dihydroxybenzophenone (6.42g, 30mmol), the viscosity modifier resin monomer (10.24g, 33mmol), water-carrying toluene (12.0mL) and catalyst K2CO3 (5.39g, 39mmol) were added to the solvent TMS (40.0mL), and stirred at 170°C and 100rpm for 2 hours under the protection of inert gas (nitrogen), and the water generated by the reaction was removed, and then the temperature was raised to 220°C at a rate of 1°C / min while stirring at 200rpm, and the polymerization reaction was carried out for 10 hours under the stirring condition of 240rpm to obtain a polymer solution. The polymer solution was poured into a large amount of deionized water while hot (the volume ratio of the polymer solution to deionized water was 1:8), and the solid-liquid separation was performed to obtain a solid polymer powder, and the solid polymer powder was crushed, and then extracted with boiling ethanol 10 times, washed with boiling deionized water 10 times, and dried at 110°C for 11h to obtain the viscosity modifier resin, the structure of which is shown in Formula I.
[0115] (2) Preparation of copolymerized polyetherketone ultra-thin film raw materials:
[0116] In terms of mass fractions, 100 parts of copolymerized polyether ketone polymer, 4 parts of viscosity modifier resin prepared in Example 1, 0 (or 0.05 or 0.1) parts of heat stabilizer and 0 (or 1 or 2) parts of lubricant were mixed by a planetary mixer for 1 hour, dried at 150°C for 4 hours, and then added to a twin-screw extruder preheated to 390°C. The screw speed (70rpm), screw feeding speed (40rpm), barrel temperature (front section 280°C, middle section 365°C, rear end 385°C), and die temperature (390°C) were controlled. The obtained mixture was extruded from the die, cooled after being shaped by the die, and granulated after being solidified to obtain a copolymerized polyether ketone ultra-thin film raw material (referred to as copolymerized PEK).
[0117] Example 3
[0118] (1) Preparation of viscosity modifier resin:
[0119] 4,4'-dihydroxybenzophenone (6.42g, 30mmol), the viscosity modifier resin monomer (11.17g, 36mmol), water-carrying toluene (12.6mL) and catalyst K2CO3 (5.39g, 39mmol) were added to the solvent TMS (41.9mL), and stirred at 170°C and 100rpm for 2 hours under the protection of inert gas (nitrogen), and the water generated by the reaction was removed, and then the temperature was raised to 220°C at a rate of 1°C / min while stirring at 200rpm, and the polymerization reaction was carried out for 10 hours under the stirring condition of 240rpm to obtain a polymer solution. The polymer solution was poured into a large amount of deionized water while hot (the volume ratio of the polymer solution to deionized water was 1:8), and the solid-liquid separation was performed to obtain a solid polymer powder, and the solid polymer powder was crushed, and then extracted with boiling ethanol 10 times, washed with boiling deionized water 10 times, and dried at 110°C for 11h to obtain the viscosity modifier resin, the structure of which is shown in Formula I.
[0120] (2) Preparation of copolymerized polyetherketone ultra-thin film raw materials:
[0121] In terms of mass fractions, 100 parts of copolymerized polyether ketone polymer, 6 parts of viscosity modifier resin prepared in Example 1, 0 (or 0.05 or 0.1) parts of heat stabilizer and 0 (or 1 or 2) parts of lubricant were mixed by a planetary mixer for 1 hour, dried at 150°C for 4 hours, and then added to a twin-screw extruder preheated to 400°C. The screw speed (70rpm), screw feeding speed (40rpm), barrel temperature (front section 280°C, middle section 365°C, rear end 385°C), and die temperature (390°C) were controlled. The obtained mixture was extruded from the die, cooled after being shaped by the die, and granulated after being solidified to obtain a copolymerized polyether ketone ultra-thin film raw material (referred to as copolymerized PEK).
[0122] Table 1 9 groups of formulas of copolymerized polyetherketone ultra-thin film raw materials in Examples 1 to 3 (parts by mass)
[0123]
[0124]
[0125] The viscosity of the copolymerized polyetherketone ultra-thin film raw materials of the 9 groups of formulations in Table 1 was tested, and the results are as follows: Figure 3 As shown. Figure 3 It can be seen that the viscosity modifier effectively reduces the processing viscosity of the resin. At the same time, the shear viscosity decreases more with the increase of viscosity modifier and content. The addition of heat stabilizer further reduces the viscosity of the material. Especially at low shear rate, the viscosity modifier has obvious effect.
[0126] Example 4
[0127] The method for preparing the copolymerized polyetherketone ultra-thin film in this embodiment comprises the following steps:
[0128] The copolymer polyether ketone ultra-thin film raw material is tape-casted to obtain the copolymer polyether ketone ultra-thin film; the feeding section of the extruder is temperature-controlled at 350°C, the compression section is temperature-controlled at 400°C, the homogenization section is temperature-controlled at 410°C, the melt pump and the filter screen are temperature-controlled at 400°C, the extrusion die head is temperature-controlled at 400°C, the screw torque is 70Nm, the screw feeding speed is 40rpm, the screw speed is 70rpm, and the hot roller temperature is 160°C; when the feeding speed and the heating temperature of each section are constant, the thickness of the copolymer polyether ketone ultra-thin film is regulated by the traction speed (5m / min); after molding, the copolymer polyether ketone ultra-thin film is rolled up to obtain the copolymer polyether ketone ultra-thin film with a thickness of 15μm and a film width of 10.6cm, and its appearance is as shown in FIG. Figure 4 As shown. Figure 4 It can be seen that its appearance transparency is good.
[0129] The copolymerized polyetherketone ultra-thin film prepared in this example was analyzed by infrared spectroscopy. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that 1649cm -1 The peak at 1234 cm is the stretching vibration peak of C═O in the polyetherketone molecule; -1 It is the Ar-O-Ar (Ar is aromatic) stretching vibration absorption peak in the polyetherketone molecule, which proves that the copolymerized polyetherketone ultra-thin film prepared in this example is consistent with the structure of pure polyetherketone.
[0130] The dynamic thermomechanical properties of the copolymerized polyetherketone ultra-thin film prepared in this embodiment were tested. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the glass transition temperature of the copolymerized polyetherketone film prepared in this embodiment reaches 159°C, which is about 15°C higher than that of ordinary polyaryletherketone materials (such as polyetheretherketone materials), indicating that the film material provided by the present invention has stronger high temperature resistance and higher operating temperature.
[0131] The mechanical properties of the copolymerized polyetherketone ultra-thin film prepared in this embodiment were tested, and the results are shown in Table 2.
[0132] Table 2 Mechanical properties test results of copolymerized polyetherketone ultra-thin films
[0133]
[0134]
[0135] It can be seen from Table 2 that the copolymerized polyetherketone ultra-thin film prepared in this embodiment has a tensile strength of 100±2 MPa and an elongation at break of 194%, which proves that the copolymerized polyetherketone ultra-thin film of the present invention has good mechanical strength and toughness.
[0136] Application Example 1
[0137] Acoustic diaphragm application - earphone core preparation and performance testing
[0138] The earphone core product was obtained by laminating a single-layer copolymer PEK film with a thickness of 9 μm and testing the frequency response (SPL) curve. The results are as follows Figure 7 As shown in the upper part of the figure, it can be seen that the SPL curve of the earphone core product assembled with the copolymerized polyetherketone ultra-thin film of the present invention is close to that of the AAC earphone core product, but the standard deviation is greater than that of the AAC product.
[0139] Application Example 2
[0140] Acoustic diaphragm application - receiver preparation and performance testing
[0141] The receiver product was obtained by hand laminating with 9μm thick copolymer PEK-glue-TPU and then laminating and assembling. The SPL curve was tested. The results are as follows Figure 7 As shown in the middle part of the figure, it can be seen that the receiver product assembled with the copolymerized polyetherketone ultra-thin film of the present invention has a SPL curve with a low frequency region which is significantly lower than that of the AAC product.
[0142] Application Example 3
[0143] Acoustic diaphragm application - speaker preparation and performance testing
[0144] The copolymer PEK (9 μm)-silica gel-PEEK (5 μm) was laminated to make the laminated film smooth and free of bubbles. After the laminated film was laminated, the film was pressed and assembled to obtain a speaker product. The SPL curve was tested. The results are as follows: Figure 7 As shown in the lower part of , it can be seen that the SPL curve of the copolymerized polyetherketone ultra-thin film sample speaker of the present invention is slightly lower than that of the AAC product in the low frequency region.
[0145] It can be seen from the above embodiments that the copolymerized polyetherketone ultra-thin film provided by the present invention has excellent high temperature resistance and high toughness, and outstanding high temperature wear resistance.
[0146] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A copolymerized polyetherketone ultra-thin film raw material, characterized in that: Calculated by weight, it includes 100 parts of copolymerized polyetherketone polymer, 2 to 6 parts of viscosity modifier resin, 0 to 1 part of heat stabilizer and 0 to 2 parts of lubricant; The structure of the viscosity modifier resin is shown in Formula I: In formula I, the value range of n is 10-60.
2. The copolymerized polyetherketone ultra-thin film raw material according to claim 1, characterized in that: The structure of the copolymerized polyetherketone polymer is shown in Formula A: In formula A, x=1 to 10%.
3. The copolymerized polyetherketone ultra-thin film raw material according to claim 1, characterized in that: The preparation method of the viscosity modifier resin comprises: mixing 4,4'-dihydroxybenzophenone, a viscosity modifier resin monomer, a water-carrying agent, a catalyst and a first solvent, and sequentially performing azeotropic dehydration and polymerization reaction; The structure of the viscosity modifier resin monomer is shown in Formula II:
4. The copolymerized polyetherketone ultra-thin film raw material according to claim 3, characterized in that: The molar ratio of the viscosity modifier resin monomer to 4,4'-dihydroxybenzophenone is 1.0-1.25:1; the volume ratio of the water-carrying agent to the first solvent is 15-30:100; and the molar ratio of the catalyst to 4,4'-dihydroxybenzophenone is 1.0-1.5:
1.
5. The copolymerized polyetherketone ultra-thin film raw material according to claim 3 or 4, characterized in that: The temperature of the azeotropic dehydration reaction is 160-180°C, and the insulation reaction time is 1-3 hours; The polymerization reaction temperature is 220-230° C., and the heat preservation reaction time is 8-12 hours.
6. The method for preparing the copolymerized polyetherketone ultra-thin film raw material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The copolymerized polyetherketone polymer, viscosity modifier resin, heat stabilizer and lubricant are mixed and dried to obtain a premix; the premix is melt-extruded and granulated to obtain the copolymerized polyetherketone ultra-thin film raw material.
7. The preparation method according to claim 6, characterized in that: The melt extrusion is twin-screw extrusion; the equipment used for the twin-screw extrusion is a twin-screw extruder; the temperature of the front section of the barrel of the twin-screw extruder is 280-290°C, the temperature of the middle section of the barrel is 355-365°C, the temperature of the rear end of the barrel is 370-385°C, and the die temperature is 380-400°C; the screw speed of the twin-screw extruder is 60-80rpm, and the screw feeding speed is 40-45rpm.
8. A copolymerized polyetherketone ultra-thin film, characterized in that: It is prepared from a copolymerized polyether ketone ultra-thin film raw material; the copolymerized polyether ketone ultra-thin film raw material is the copolymerized polyether ketone ultra-thin film raw material according to any one of claims 1 to 5 or the copolymerized polyether ketone ultra-thin film raw material obtained by the preparation method according to any one of claims 6 to 7; the thickness of the copolymerized polyether ketone ultra-thin film is 9 to 300 μm.
9. The method for preparing the copolymerized polyetherketone ultra-thin film according to claim 8, characterized in that: The following steps are involved: The copolymerized polyetherketone ultra-thin film raw material is tape-cast to obtain the copolymerized polyetherketone ultra-thin film.
10. Application of the copolymerized polyetherketone ultra-thin film according to claim 8 or the copolymerized polyetherketone ultra-thin film obtained by the preparation method according to claim 9 in the field of acoustic diaphragms.
Citation Information
Patent Citations
Poly(ether-ketone) polymer and production method and application thereof
CN110156981A
Production of polyaryl ether ketone
JP1993032776A
Aromatic polymer having sulfonated quinoxaline structure, polymer electrolyte and proton conductive film
JP2010126603A
Cited By
Preparation method of polyether ketone amide / polyether ether ketone superfine denier monofilament
CN120082982A